Morphogenesis of Infectious Hepatitis C Virus Particles - Suzuki, Tetsuro (Frontiers in Microbiology, 2012)
More than 170 million individuals are currently infected with hepatitis C virus (HCV) worldwide and are at continuous risk of developing chronic liver diseases. Since a cell culture system that enables relatively efficiently propagation of HCV was available, findings on viral and host factors involved in HCV particle formation have been accumulating. Association of the viral Core, which forms the capsid, with lipid droplets appears to be prerequisite for the early stage of HCV morphogenesis. Maturation and release of HCV particles is tightly linked to the pathway of very-low-density lipoprotein biogenesis. Although expression of Core as well as envelope proteins E1 and E2 results in the formation of virus-like particles in heterologous expression systems, there is increasing evidence that the viral non-structural proteins and p7 are also required for the production of infectious particles, suggesting that HCV genome replication and virion assembly are closely linked. Advances in our understanding of the molecular mechanisms by which infectious HCV particle is formed are summarized.